Cyrtorhina globosa from Middle Eocene beds of ]opi in Istria, Croatia - Vasja Mikuž (Geologija, 2010)
The contribution contains the description and presentation of carapax remain of crab species Cyrtorhina globosaBeschin, Busulini, De Angeli & Tessier 1988, found in Middle Eocene – Lutetian beds near the ]opi settlementin central Istria, Croatia.